The Impact of Dividend Policy on PT Unilever Indonesia Tbk's Stock Price: EPS and DPS Analysis for the 2015–2024 Period - Yansen, Albert; Dwina, Nurmeitha; Karina, Mona (Universitas Mohammad Husni Thamrin, 2026)
National Level At the national level, the Indonesia Stock Exchange (IDX) functions as the main capital market infrastructure that provides capital access for issuers and investment facilities for the public. This study aims to analyse the effect of dividend policy on the stock price of PT Unilever Indonesia Tbk. during the 2015–2024 period, focusing on the analysis of Earnings Per Share (EPS) and Dividends Per Share (DPS). The method used in this study is quantitative with a causal nature. The research design is a time series study, as data were collected from the 2015–2024 period. Data were collected from the annual financial statements and quarterly reports of PT Unilever Indonesia Tbk, which is listed on the Indonesia Stock Exchange (IDX). Data analysis was performed using Structural Equation Modelling (SEM-PLS) techniques with the assistance of Smart PLS version 4 software to test the influence between the variables studied. The results show that stable and high dividend announcements, reflected in increases in EPS and DPS values, have a significant impact on the stock price of PT Unilever Indonesia Tbk. Furthermore, DPS functions as a mediator between EPS and stock price, thereby increasing investor attractiveness to the company. The recommendation from this study is that an effective dividend policy can provide a positive signal to the market and influence stock price dynamics, so companies need to maintain a consistent dividend policy to strengthen investor confidence and stabilize stock prices in the capital market.